Determinants of Original Local Government Revenue (PAD): Case Studies of 34 Provinces in Indonesia - Indanazulfa Qurrota A'yun; Wulan Okta Vianti; Zalina (Universitas Ahmad Dahlan, Yogyakarta, 2022)
Regional Original Revenue (PAD) is a fund received by the region from the existing resources in the area. PAD is regulated based on regional regulations in accordance with applicable laws. The higher the skill of the region in increasing regional original income, the greater the flexibility of the region to use PAD in accordance with the wishes, needs and priorities of regional development. This study aims to analyze the effect of independent variables, local taxes, regional levies, Gross Domestic Product (GRDP) and investment on PAD in 34 provinces in Indonesia from 2015 to 2018. This study uses a random effect regression analysis method and is analyzed using statistics. The results show that the variables of local taxes, regional levies and investment have a positive and significant impact on PAD in 34 provinces in Indonesia, while the variable Gross Domestic Product (GRDP) has a positive but not significant effect on PAD in 34 provinces in Indonesia.